TOPENG BONDRES INOVATIF - Sugama, I Wayan (LPPM IKIP PGRI Bali, 2019)
Topeng bondres is a new form that displays the good humor of dance or dialogue that is delivered on each appearance. This topeng bondres experienced a very rapid development that can cause a sence of concern for figures of art figures, cultural, and society in general.  To maintain its change and development, was initiated by adding new art from PKB XXXIX 2017, is topeng bondres inovatif. The Gianyar district ambassador is representated by the Gianyar Sanggar Jaba Jero featuring a new form of topeng bondres inovatif by packing a tight dollars title with a tourist destination.